Предмет: Алгебра,
автор: Дарья11978
Упростите выражение:(х+2)(х^2-4)(х-2) помогите пожалуйста)
Ответы
Автор ответа:
0
...=(x+2)(x-2)(x²-4)=(x²-4)(x²-4)=(x²-4)²=x4-8x²+16
Автор ответа:
0
Спасибо большое))
Автор ответа:
0
:)
Автор ответа:
0
^^
Автор ответа:
0
( x + 2)(x - 2)( x^2 - 4) = ( x^2 - 4)(x^2 - 4)= ( x^2 - 4)^2 = x^4 - 8x^2 + 16
Похожие вопросы
Предмет: Физика,
автор: kossemaria7
Предмет: Алгебра,
автор: Steepbread
Предмет: Литература,
автор: serebro4776
Предмет: Литература,
автор: sosnina1997
Предмет: Математика,
автор: Аноним